2007
DOI: 10.1007/s00213-007-0774-3
|View full text |Cite
|
Sign up to set email alerts
|

Reversal of PCP-induced learning and memory deficits in the Morris’ water maze by sertindole and other antipsychotics

Abstract: These results confirm that repeated PCP administration induces marked cognitive deficits. Further, second-generation antipsychotics like sertindole, clozapine, and risperidone within a certain, often narrow, dose range are able to reverse the impairment and thus might improve cognitive deficits in schizophrenic patients, whereas classical compounds like haloperidol lack this effect. The receptor mechanisms involved in the reversal of PCP's disruptive effect are discussed and likely include a delicate balance b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(47 citation statements)
references
References 58 publications
5
42
0
Order By: Relevance
“…The main advantage of this within-session cued reversal-learning model is that it allows for the rapid assessment of reversal-learning performance, with the appropriate reversal of behavior being observed over the course of a small number of trials. Despite this procedural difference, the ability Final Draft: of the tested agents to reverse PCP-induced deficits was consistent with previous reports of the cognitive-enhancing effects of SGAs in animal models in general [11,13,18,28,29,39] and in different types of reversal-learning tasks [10,28]. Furthermore, these data are fully consistent with the effects of other SGAs and novel antipsychotics that have been observed in this reversal-learning task [1][2][3]25].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…The main advantage of this within-session cued reversal-learning model is that it allows for the rapid assessment of reversal-learning performance, with the appropriate reversal of behavior being observed over the course of a small number of trials. Despite this procedural difference, the ability Final Draft: of the tested agents to reverse PCP-induced deficits was consistent with previous reports of the cognitive-enhancing effects of SGAs in animal models in general [11,13,18,28,29,39] and in different types of reversal-learning tasks [10,28]. Furthermore, these data are fully consistent with the effects of other SGAs and novel antipsychotics that have been observed in this reversal-learning task [1][2][3]25].…”
Section: Discussionsupporting
confidence: 88%
“…In one long-term naturalistic study, the Clinical Antipsychotic Trials of Intervention Effectiveness (CATIE) study, some antipsychotics produced small but statistically significant improvements in cognition [32]. In further recognition of the need to address cognitive dysfunction in patients with schizophrenia and to encourage the development of cognition-enhancing drugs for schizophrenia, the National Institute of Preclinical studies have routinely demonstrated that second-generation antipsychotics (SGAs) enhance cognitive function in animal models that assess reversal learning, working and nonspatial memory, and selective attention [1][2][3]11,18,24,25,35,39,55,56]. In a rodent operant reversal-learning paradigm based on tasks developed by Smith et al [48] and Jones et al [30], deficits in reversal learning produced Final Draft: by phencyclidine (PCP) were attenuated by the SGAs clozapine, ziprasidone, and olanzapine, but not by the first-generation antipsychotics haloperidol or chlorpromazine [2,3,25].…”
Section: Introductionmentioning
confidence: 99%
“…Certain brain regions and neurotransmitter systems including hippocampus, striatum, basal forebrain, cerebral cortex, and cerebellum play an important role in the MWM performance of rodents [33]. Different studies showed that glutamatergic NMDA receptor activity is crucial for spatial learning and memory, and antagonists of these receptors revealed cognitive impairments on the MWM test in rodents [34][35][36]. Our results indicated that sub-chronic MK-801 administration induced persistent learning deficits in the acquisition period at all of the 4 days and memory defect in the probe test.…”
Section: Discussionmentioning
confidence: 99%
“…In order to make a direct comparison, risperidone was also given subchronically. Didriksen and colleagues used doses of 0.63 and 1.3 mg/kg of clozapine for their reversal learning study as their pilot study showed worsening of performance with higher doses of clozapine in combination with PCP [14]. It has also been shown that tolerance can develop to the sedative effects of clozapine after repeated dosing [10].…”
Section: Discussionmentioning
confidence: 99%